Factors influencing Malaysian Generation Y’s intention to purchase counterfeits of luxury brands product / Norfarhana Mohamad Fuad - Mohamad Fuad, Norfarhana (Faculty of Business and Management, 2015)
Counterfeit consumption has recently attracted considerable attention as the number of counterfeit products keep rose up year by year. The study purpose is to identify the important factors influencing Malaysian Generation Y’s purchase intention towards counterfeit luxury brand products. For this study, the researcher chooses four elements which consist of attitude toward counterfeit product, subjective norms, behavioral control, and financial control. The findings of the study show that all four organizational elements have significant relationship with purchase intention. Based on the results, the researcher found that the most significant variable that influenced Malaysian Generation Y’s purchase intention towards counterfeit luxury brand products is behavioral control. The researcher suggests that the government should take serious action to solve this issue.